(untitled) (Journal of Universal Science Research, 2025)
This article examines current innovations in preschool education with a focus on the opportunities provided by artificial intelligence (AI). The study analyzes how digital tools, adaptive learning systems, intelligent assistants, and data-driven decision-making enhance early childhood learning, support teachers, and create personalized learning environments. The article also discusses the challenges of integrating AI, such as teacher preparedness, ethical concerns, and data security. Recommendations for effective and responsible AI implementation in preschool education are proposed.